Approximation of conjugate differentiable functions by biharmonic Poisson integrals - Zhyhallo, K. M.; Kharkevych, Yu. I. (Ukrains’kyi Matematychnyi Zhurnal, 2009)
We determine the exact values of upper bounds of approximations by biharmonic Poisson integrals on classes of conjugate differentiable functions in uniform and integral metrics.